Predicting students’ math self-concepts to explain gender differences through teachers’ judgments and students’ perceived teachers’ judgments - Reschke, Katharina; Steinmayr, Ricarda; Spinath, Birgit (Frontiers in Education, 2023)
The present study examined to what extent teachers' judgments of students' aptitude and students' perceived teachers' judgments explain gender differences in the early development of students' math self-concepts. A sample of N = 519 elementary school students was investigated at four measurement occasions from the end of third until the end of fourth grade. We assessed students' self-concepts and their perceived teachers' judgments of their aptitude in math. Teachers (N = 27) judged students' aptitude in math and provided students' math grades. First, we found significant gender differences in students' math self-concepts, teachers' judgments, and students' perceived teachers' judgments, but not in students' math grades. Second, structural equation models showed that teachers' judgments of students' aptitude as well as students' perceived teachers' judgments of students' aptitude longitudinally predicted students' self-concepts. Mediation analyses demonstrated that teachers' judgments and students' perceived teachers' judgments contributed to gender differences in students' math selfconcepts. Implications for future research and practice are discussed.